The ministry of the ephemeral priest in educational institutions - Vasilev, Ivaylo (Forum Theologicum Sardicense, 2025)
Ivaylo Vasilev, The ministry of the ephemeral priest in educational institutions. The article addresses questions about the foundation and characteristics of priestly ministry within an educational environment, examining the activities, personality, and sacramental aspects of the priest’s role. The study focuses on the temporary ministry at the Theological Faculty of Sofia University, where a longer practice of spiritual care, including work with seminaries, has been established.